1997
DOI: 10.1007/s001170050282
|View full text |Cite
|
Sign up to set email alerts
|

Patient acceptance of high-field whole-body MR systems, open MR systems and dedicated MR systems for the extremities

Abstract: To our knowledge no comparative studies investigating patients' acceptance of different MR systems have been published. We therefore studied a number of subjective criteria to evaluate both patients' acceptance of and subjective conditions during magnetic resonance imaging (MRI) studies. MRI studies were performed using four separate systems. Two were conventional body MR systems operating at 1.0 or 1.5 Tesla, another was a 0.2 Tesla open whole-body MR system, and the last was a 0.2 Tesla MR system dedicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
0
8
0
2
Order By: Relevance
“…Mehdizade et al found that diffusion-weighted MR imaging performed with a low-field open MR scanner was reliable for the evaluation of acute stroke [32]. Regarding the restrictions of conventional MR imaging, horizontal open MR scanners have shown potential for facilitating imaging of patients with claustrophobia or extreme obesity [5], [7], [8], and a better patient acceptance is assumed for open MR scanners [5], [10], [11]. Reduced claustrophobia rates have also been found with recent short-bore MR scanners [2], [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mehdizade et al found that diffusion-weighted MR imaging performed with a low-field open MR scanner was reliable for the evaluation of acute stroke [32]. Regarding the restrictions of conventional MR imaging, horizontal open MR scanners have shown potential for facilitating imaging of patients with claustrophobia or extreme obesity [5], [7], [8], and a better patient acceptance is assumed for open MR scanners [5], [10], [11]. Reduced claustrophobia rates have also been found with recent short-bore MR scanners [2], [9].…”
Section: Discussionmentioning
confidence: 99%
“…Most notable differences were found in overall image quality, mean SNR values, and quantitative contour sharpness. Previous studies have shown an advantage of open MR scanners regarding patient acceptance and imaging of claustrophobic or obese patients [5], [6], [7], [10], [11]. However, high claustrophobia rates have recently been found in patients at risk for both open and short-bore MR imaging [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heuck et al compared two high-field closed MR systems operating at 1.5-T and 1.0-T with an open whole-body scanner and a dedicated extremity MR system, both operating at 0.2-T [37]. In 40 patients examined on each system (160 total) they found a mainly positive condition and acceptance for all MR scanners.…”
Section: Discussionmentioning
confidence: 99%
“…They found a lower rate of sedation and an eased biomonitoring of the patient. According to Hayashi et al and Heuck et al, lowfield systems offer far lower costs at no or a neglectable loss of diagnostic performance [25,26].…”
Section: Low-/mid-field Ce-mramentioning
confidence: 99%